Analysis of the Use of Website-based Couple Therapy Module in TB Patients in Coastal Areas - Muhsinah, Sitti; Rini, Dewi Sartiya; Wijayati, Fitri (Poltekkes Kemenkes Palu, 2023)
The Couple Therapy module is based on the website as a form of intervention for TB patients in dealing with sexual needs. Key components of this web-based couple therapy module include programme content, use of multimedia, interactive online activities, and provision of feedback support. This study aimed to analyze the use of a website-based Couple Therapy Module on Pulmonary TB patients in the Coastal Area of Nambo District. The method used in this study is a combined research/combination of quantitative and qualitative (mixed-method), namely concurrent triangulation design (a balanced mixture of quantitative and qualitative) with a total of 20 respondents. The results of the study quantitatively showed that the couples therapy website had a positive impact marked by 90% of respondents stating that the website is easily accessible, has an attractive appearance, updated information and is interactive because it provides online consultation features. This is confirmed by participants' expressions regarding participants' perceptions of this website. Positive perception shows the expression of participants stating that the website is easily accessible, attractive display, fast access to information and interesting information. Negative perceptions show the expression of participants stating that it is difficult to open the website. The conclusion of this study is that website-based educational media is one of the right solutions in transferring health information to pulmonary TB patients.